COMPARISON OF PAIN DEGREES USING VISUAL ANALOG SCALE (VAS) IN VARICOCELE PATIENT AFTER MICROSURGERY VARICOLECTOMY COMPARED TO NON MICROSURGERY VARICOCELECTOMY PROCEDURE AT HASAN SADIKIN HOSPITAL BANDUNG IN 2014 – 2015 - Nurgoho, Firman; Noegroho, Bambang Sasongko; Adriansjah, Ricky (Indonesian Urological Association, 2020)
Objective: This study aimed to report the demographic, presentation, and compare the pain degree after varicocelectomy procedure at Hasan Sadikin Hospital Bandung from 2014 until 2015. Material & Methods: We study the demographic, presentation, and outcome of varicocelectomy to pain degree in patient who came to Hasan Sadikin Hospital Bandung from 2014 until 2015. Results: The mean age of patients was 29.43 years old. Patient consist of 2 (2.89%) patients with varicocele grade I, 32 (46.37 %) patients with varicocele grade II, 33 (47.82%) patients with varicocele grade III, and 2 (2.89 %) with varicocele grade IV. We found incidences of varicocele at the right side in 1 (1.44 %) patient, at the left side in 34 (49.27%) patients, and at bilateral in 34 (49.27%) patients. Thirty eight patients (55%) patients underwent non-microsurgical varicocelectomy and 31 (45%) patients underwent microsurgical varicocelectomy. 22 (57.89%) patients still had pain after non microsurgical varicocelectomy and 30 (96.77%) patients had no pain after microsurgical varicocelectomy. Only one (4.34%) patient experienced scrotal pain after microsurgical varicocelectomy but the pain relieves after 6 months postoperative. Conclusion: Microsurgical varicocelectomy is an effective treatment of varicocele. Our comparative study among open surgical and microsurgical varicocelectomy has confirmed microsurgical varicocelectomy has a better postoperative outcome.